Iodine promoted one-pot synthesis of flavones - Darvin Jesús Torres Ribón; Luis Fernando Roa de la Fuente; Nancy Romero Ceronio; Oswaldo Hernández Abreu; Madeleyne Ramos Rivera; Jorge R. Juárez; Rosalía Torralba; Manuel Velasco Ximello; Quirino Torres Sauret; Cuauhtémoc Alvarado Sánchez (Results in Chemistry)
A novel one-pot methodology for the synthesis of flavones starting from simple precursors such as 2′-hydroxyacetophenone and benzaldehyde derivatives in pentan-1-ol (a green solvent), without additives, mediated by iodine and with short reaction times (1 h) is described. A scope of 21 products in yields ranging from 28 % to 90 % is presented. Results demonstrated that the yield was enhanced by the use of benzaldehyde derivatives with activating substituents on the para-position.